2012
DOI: 10.4236/ojn.2012.21004
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychological distress of Public Health Nurse in Kagawa prefecture, Japan: A pilot study

Abstract: We evaluated the psychological distress using a scale of the K6, the 6-item scale of psychological distress on public health nurse in Kagawa prefecture, Japan. We send the questionnaire to all public health nurses (n = 419) in Kagawa prefecture. Then, a total of 256 public health nurses (1 man and 255 women), had completely answered the questionnaires, were analyzed in a cross-sectional investigation study. The association between psychological distress and considerable factors were evaluated by using the K6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…As previously shown (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), the questionnaires for clinical psychologists consisted of the following details in sequence: sex, age, duration of experience as a clinical psychologist, classi cation of clinical eld (Japanese Society of Certi ed Psychologists, 2009), (Medical, health, welfare eld/Educational eld/University, research institution/Justice, legal, police eld/Industry, labor eld/Private practice), and other certi cations (Japanese Society of Certi ed Psychologists, 2009), (Physician/Nurse/Certi ed social worker, psychiatric social worker/Speech therapist/ Teacher/Other). In addition, we evaluated the consciousness of suicide among clients (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), anxiety about preventing suicide (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), and frequency of receiving supervision (Japanese Society of Certi ed Psychologists, 2009), and participating in a case study by asking the following questions: 1) Do you ever worry about suicide of clients in your daily work as a clinical psychologist? (most of the time/some of the time/a little of the time/none of the time) 2) If you had to do something individually to prevent the suicide of a client (clients) in your daily work as a clinical psychologist, how much anxiety would you feel?…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…As previously shown (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), the questionnaires for clinical psychologists consisted of the following details in sequence: sex, age, duration of experience as a clinical psychologist, classi cation of clinical eld (Japanese Society of Certi ed Psychologists, 2009), (Medical, health, welfare eld/Educational eld/University, research institution/Justice, legal, police eld/Industry, labor eld/Private practice), and other certi cations (Japanese Society of Certi ed Psychologists, 2009), (Physician/Nurse/Certi ed social worker, psychiatric social worker/Speech therapist/ Teacher/Other). In addition, we evaluated the consciousness of suicide among clients (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), anxiety about preventing suicide (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), and frequency of receiving supervision (Japanese Society of Certi ed Psychologists, 2009), and participating in a case study by asking the following questions: 1) Do you ever worry about suicide of clients in your daily work as a clinical psychologist? (most of the time/some of the time/a little of the time/none of the time) 2) If you had to do something individually to prevent the suicide of a client (clients) in your daily work as a clinical psychologist, how much anxiety would you feel?…”
Section: Methodssupporting
confidence: 63%
“…Kuriyama et al (2009) reported that the percentage of participants with high psychological distress was 6.7 using the K6 in community-dwelling people aged 40 years or older living in Japan. Suzue et al (2011), Sakano et al (2012), and Miyamae et al (2013) also showed that the percentages of medical doctors, public health nurses, and school teachers with high psychological distress by using the K6 were 6.0 , 5.9 , and 8.2 , respectively, in Kagawa Prefecture, Japan. Among Japanese employees in Akita Prefecture, Japan, 10.8 showed high psychological distress (Fushimi et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…We also showed that the rates of medical doctors and public health nurses with psychological distress by using the K6 were 6.0% and 5.9% in Kagawa prefecture, Japan [18,19]. Fushimi et al reported that 10.8% of Japanese employees had high psychological distress in Akita prefecture, Japan [20].…”
Section: Discussionmentioning
confidence: 94%
“…In this study, a total of 8.2% of school teachers were defined as having psychological distress in Kagawa prefecture, Japan. Therefore, the rate of school teachers with psychological distress was higher than that of Japanese general people, medical doctors and public health nurses [17][18][19], and similar to that of Japanese employees [20]. According to data on the mental health of school teachers in Japan, the proportion of teachers with minor psychiatric disorders was higher than that among civil servants [6] by using the Japanese version of the General Health Questionnaire (GHQ) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Using the K6 questionnaire, we have previously evaluated psychological distress of public health nurses [15], school teachers [16], and medical doctors [17] in Kagawa Prefecture, Japan, in a cross-sectional study, and 5.9, 8.2, BMI body mass index (kg/m 2 ), SBP systolic blood pressure (mmHg), DBP diastolic blood pressure (mmHg) and 6.0 %, respectively, were defined as having psychological distress [15][16][17]. In community dwelling Japanese, the prevalence of psychological distress has been reported to be 6.7 % [18].…”
Section: Discussionmentioning
confidence: 99%